If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 4(21 + -8x) = 18 -1x + (21 * 4 + -8x * 4) = 18 -1x + (84 + -32x) = 18 Reorder the terms: 84 + -1x + -32x = 18 Combine like terms: -1x + -32x = -33x 84 + -33x = 18 Solving 84 + -33x = 18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-84' to each side of the equation. 84 + -84 + -33x = 18 + -84 Combine like terms: 84 + -84 = 0 0 + -33x = 18 + -84 -33x = 18 + -84 Combine like terms: 18 + -84 = -66 -33x = -66 Divide each side by '-33'. x = 2 Simplifying x = 2
| -3x-16=-6x-25 | | 7(-x-2)=-7x+7 | | -0.6x+2.4(-4+4y)=2.4 | | 0.3x-1.2y=-1.2 | | x=2(115-x)+10 | | 2(5x-26)=10x-52 | | x+(x+4)=2x-1 | | -9x+3(5x-2)=-6 | | 5(a-1)= | | 0.65x+0.2(18-x)=0.3(18) | | 2x+205=11x-11 | | 157-5x=31x+17 | | 1z^2+9z-36=0 | | 8x-2+x-4= | | -2y+2x=14 | | -2x+2y=14 | | -4x=4x-4+3 | | 4x+81=-22 | | 4x+12+3=(2x-3)(2x+3) | | 4y+x=-22 | | 4x+y=-22 | | 3x^2-7x+K^2-2K=0 | | x+y=175 | | y+x=20 | | 4x(x+3)+3=(2x-3)(2x+3) | | -2.4y+0.1x=10.5 | | -2.4x+0.1y=10.5 | | 2y+3x^3-5x-y^2+3xy=8 | | 5y=-5x+10 | | 6y=6x+6 | | 6x=6y+6 | | .25(8z-4)=z+8-22 |